Behaviors Characteristic of Autism Spectrum Disorder in a Geriatric Cohort With Mild Cognitive Impairment or Early Dementia. (January 2020) - Rhodus, Elizabeth K.; Barber, Justin; Abner, Erin L.; Duff, Danielle M.C.; Bardach, Shoshana H.; Caban-Holt, Allison; Lightner, Donita; Rowles, Graham D.; Schmitt, Frederick A.; Jicha, Gregory A.
Abstract : Introduction: Autism spectrum disorder (ASD) represents a heterogenous cluster of clinical phenotypes that are classically diagnosed by the time of adolescence. The possibility of late-life emergence of ASD has been poorly explored. Methods: To more fully characterize the possibility of late-life emergence of behaviors characteristic of ASD in mild cognitive impairment and AD, we surveyed caregivers of 142 older persons with cognitive impairment from the University of Kentucky Alzheimer's Disease Center Longitudinal Cohort using the Gilliam Autism Rating Scale-2. Results: Participants with high autism index ratings (autism "possible/very likely, " n=23) reported significantly (statistically and clinically) younger age at the onset of cognitive impairment than those who scored in the autism "unlikely" range (n=119): 71.14±10.9 vs. 76.65±8.25 ( P =0.034). In addition, those in the autism "possible/very likely" group demonstrated advanced severity of cognitive impairment, indicated by the Clinical Dementia Rating Scale Sum of Boxes scores. Discussion: Data demonstrate that ASD behaviors may seem de novo of degenerative dementia and such behaviors are more prevalent in those with early onset dementia. Further work elucidating a connection between ASD and dementia could shed light on subclinical forms of ASD, identify areas of shared neuroanatomic involvement between ASD and dementias, and provide valuable insights that might hasten the development of therapeutic strategies.